2001
DOI: 10.1152/jn.2001.86.4.2011
|View full text |Cite
|
Sign up to set email alerts
|

Surround Suppression in Primate V1

Abstract: We investigated the spatial organization of surround suppression in primate primary visual cortex (V1). We utilized drifting stimuli, configured to extend either from within the classical receptive field (CRF) to surrounding visual space, or from surrounding visual space into the CRF or subdivided to generate direction contrast, to make a detailed examination of the strength, spatial organization, direction dependence, mechanisms, and laminar distribution of surround suppression. Most cells (99/105, 94%) throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
242
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(273 citation statements)
references
References 54 publications
30
242
0
1
Order By: Relevance
“…Several previous studies have examined spatial organization of the CRF and surround by presenting one patch in the CRF and another patch at one of several locations outside the CRF (Cavanaugh et al 2002b;Jones et al 2001;Vinje and Gallant 2000;Walker et al 1999). In these studies, the boundary between the CRF and the surround was typically determined from a size-tuning curve or as a circumference outside which a stimulus was ineffective if presented to the surround alone.…”
Section: Consideration On the Present Methods In Comparison With Othermentioning
confidence: 99%
“…Several previous studies have examined spatial organization of the CRF and surround by presenting one patch in the CRF and another patch at one of several locations outside the CRF (Cavanaugh et al 2002b;Jones et al 2001;Vinje and Gallant 2000;Walker et al 1999). In these studies, the boundary between the CRF and the surround was typically determined from a size-tuning curve or as a circumference outside which a stimulus was ineffective if presented to the surround alone.…”
Section: Consideration On the Present Methods In Comparison With Othermentioning
confidence: 99%
“…Analysis of two macaque monkeys was performed while animals were anesthetized [sufentanil 4 g蜑kg per hour or halothane (0.1-0.4%) in 70% N 2 O蜑30% O 2 ] and paralyzed (0.1 mg蜑kg per hour vecuronium bromide) by using published methods (16). After intravitreal SSP administration (2.5, 5.0, 7.5, and 10 g in 50 l), animals were imaged for at least 6 h.…”
Section: Ocular Hypertension (Oht)mentioning
confidence: 99%
“…Furthermore, neurophysiological studies have also showed that, once a cell is activated by a stimulus in its classical receptive field (CRF), another, simultaneously presented stimulus outside that field can have an effect on the cell response (Blakemore and Tobin 1972;Knierim and van Essen 1992;Nothdurft et al 1999;Jones et al 2001). This, mostly inhibitive, effect is known as nonclassical receptive field inhibition or surround suppression.…”
mentioning
confidence: 99%
“…A further aim of the current work is to explore some functional aspects of surround suppression in motion processing using a computational model. Surround interactions are observed in different cortical regions such as V1 Jones et al 2001, middle temporal (MT/V5) (Allman et al 1985;Raiguel et al 1995) and lateral medial superior temporal (MST) (Eifuku and Wurtz 1998), which are areas involved in processing motion information. Also, it is known that the RFs of about one half of the cells in MT have antagonistic surrounds (Allman et al 1985;Tanaka et al 1986;Raiguel et al1995;Bradley and Anderson 1998;Born 2000;DeAngelis and Uka 2003;Born and Bradley 2005).…”
mentioning
confidence: 99%